SYMBOLIC INTERACTION: MARKETING PUBLIC RELATIONS IN PRIVATE ISLAMIC UNIVERSITY - Tresna Wiwitan (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2021)
Marketing Public Relations (Marketing PR) activities, this includes universities Marketing PR is a synergy between marketing activities and public relation strategy. This concept does not only market or sell product/service but also create, nurture and maintain the institution’s positive image. Bandung Islamic University (Unisba) is one of the private islamic universities implementing Marketing PR activities. The objective of this research is to acknowledge and to analyze: 1) The meaning of Marketing PR to Public Relations and Promotional Team, 2) The experience of Public Relations and Promotional Team in conducting the Marketing PR activities. This research uses qualitative research, constructivist paradigm with a phenomenology approach. The theory used is the symbolic interaction, sampling technique is conducted purposively. The result of this research explains that; based on the experience, Public Relations and promotional team must have managerial, public speaking and public relations capabilities in educating High School students.